Changes in seabed mining - Hein, James (2021)
• The present chapter provides an update to chapter 23 of the first World Ocean Assessment (United Nations, 2017a) in terms of shallow-water aggregate, placer deposits, ironsand deposits and phosphorite deposits. It focuses on exploration licences for deepwater seabed mineral resources, the number of which has increased significantly since the first Assessment. • New technologies to reduce impacts on the marine environment are now envisaged for the exploitation of placer deposits, traditionally mined by dredging. Prospects for mining phosphorite deposits have faced opposition from stakeholders and have yet to become a reality. • Seabed mineral deposits covered in the present chapter (polymetallic nodules, polymetallic sulphides and cobalt-rich ferromanganese crusts) are being considered for mining and the object of 30 contracts for exploration awarded by the International Seabed Authority (ISA). • One driver for those activities is that deepwater seabed mineral resources contain diverse rare and critical metals that would support the implementation of Sustainable